Effective measures for minimizing playing-related musculoskeletal disorders among tertiary education student pianist in Malaysia - Hamedon, Titi Rahmawati; Chia, Ying Ling; Loo, Fung Chiat (Springer Link, 2019)
The risk of developing playing-related musculoskeletal disorders (PRMD) can be reduced by taking break in between practicing sessions. The study aimed to determine the level of knowledge on PRMD and its associated factors. The cross-sectional study was done among 192 randomly selected subjects. Data was collected by face to face interview method using pre tested questionnaire. Most of respondents are female (84.9%), young (median age is 20 years), practice piano for <3 h/day (53.1%) and 91.7% of them take break in between their practice. Most of them are aware of PRMD (76%) and most heard it from their teachers. Significant association was found between PRMD and practice habit of <3 h/day, taking break in between practice, doing physical cool down after practice and taking dietary supplements. This finding indicate that simple measures like limiting the duration of piano practice time and taking break in between practicing piano can help to prevent muscle tiredness that may contribute to PRMD.